Frozen Cartoon Film as a Learning Media to Improve the Students' Pronunciation Ability - Shilvyna Rahma; Husni Mubarok (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
Pronunciation is an important factor in measuring achievement in learning speaking in English. Proof of speaking fluency by students is shown when they communicate verbally with a native speaker. This study aims to explain the use of the Frozen cartoon film as a learning medium to improve the students’ pronunciation ability. The research focuses are the Frozen 1 cartoon synopsis, the stages, and procedures for implementing the dubbing and subtitling method and screening the film using the dubbing method. This study uses a descriptive research method with a qualitative approach. Data collection was carried out by library research (library research). Sources of data in the form of written materials consist of primary data sources and secondary data sources. The validity of the data test emphasizes the validity and reliability test. The results of the study were analyzed using the content analysis method. The results showed that the cartoon "Frozen" as a learning medium was very appropriate to be practiced in improving students' pronunciation skills. This media provides several benefits: (a) being a solution in communicating English orally, (b) providing interesting, attractive teaching media, and (c) choosing the right learning method so that it is effective for students. The presentation of the “frozen” cartoon is packaged with interesting storyline pictures and audio sound that makes students involved in the film. The dubbing and subtitling methods are learning methods to motivate students to communicate in English. Effective and efficient media and methods can help students engage in learning English and at the same time be motivated to communicate in English.